1999
DOI: 10.1046/j.1365-2559.1999.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins and neurotrophin receptors in some neural crest‐derived tumours (ganglioneuroma, phaeochromocytoma and paraganglioma)

Abstract: The pattern of expression of neurotrophins and neurotrophin receptors in the analysed tumours basically matches that of sympathetic neurones, adrenal chromaffin cells and paraganglionic cells, and suggests responsiveness of these cells to neurotrophins. Nevertheless, the function of TrkA and TrkC in regulating the biology of these tumours, if any, remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…54,55 RT-PCR results and results from immunohistochemistry (also at lower antibody dilutions), however, suggest additional expression sites. Low titers of BDNF, NT-4/5, and Trk-A mRNA transcripts and high titers of NT-3 transcripts were found in rat hepatocytes (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…54,55 RT-PCR results and results from immunohistochemistry (also at lower antibody dilutions), however, suggest additional expression sites. Low titers of BDNF, NT-4/5, and Trk-A mRNA transcripts and high titers of NT-3 transcripts were found in rat hepatocytes (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Pello et al [ 30 ] were unable to demonstrate the NT-3 presence on the CB of adult human subjects by immunohistochemistry. The immunopositivity for NT-3 was later demonstrated by Atanasova and Lazarov [ 20 ] in rat CB ( Table 1 ).…”
Section: Nerve Growth Factor Familymentioning
confidence: 99%
“…Even though NGF production has been observed in a variety of normal tissues (Santambrogio et al, 1994;Kokaia et al, 1993;Pincelli et al, 1997;Nilsson et al, 1997), very few investigators have found NET cells of neuroblastic phenotype that produce and secrete active NGF (for review see Vinores and Perez Polo, 1983). Even when NET cells seem to produce bioactive NGF, the levels are insufficient to activate the most sensitive receptors (Gill et al, 1998) or are completely undetectable (Pello et al, 1999). This is not surprising, insofar as NGF exerts a differentiating effect on immature neuroblasts, and production by tumor cells of neuroblastic origin would be disadvantageous for their growth.…”
mentioning
confidence: 99%